PREPARATION OFNb BASED THIN FILM USING PULSED LASER DEPOSITIONAND ITS ELECTRICAL PROPERTY - Salim Mustofa; Saeful Yusuf (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2013)
PREPARATION OFNb BASED THIN FILM USING PULSED LASER DEPOSITIONAND ITS ELECTRICAL PROPERTY. The research for largering capacity of dielectric multi layer type capacitor using Pulsed Laser Deposition (PLD) method was carried out. In this study, we focus on the inexpensive material Nb as a substitute for expensive material Ta, which is currently used for ferroelectric material. The Nb-based (Nb2O5) and TiO2 particle were deposited on Si/SiO2 substrate at temperature of 600 oC under the oxygen pressure of 5Pa, and Pt was used as the last layer. Doping of TiO2 to the Nb2O5was carried out by alternately replacing each target and finally the deposited film with a thickness of 200 nm was achieved. The capacity value of pure Nb2O5 thin film was higher than pure TiO2 , but TiO2 was more stable against the changes of temperature. The capacitor that has a ratio of 30% Nb2O5 showed the highest capacity value. Single layer of Nb2O5 thin film has the largest rate of change in capacitance, and the capacitor that already doped by TiO2 has a more less changes in capacitance against the changes of temperature. In order to crystallize, the capacitor was then annealed in the air for 12 hours at the temperature of 700o . Same as before annealing, a mixed thin film thas has a ratio 30% of Nb2O5 still showed the highest capacity value, even there is a small changes against the against the changes of temperature. Other mixed thin film with different ratio of TiO2 have more stable temperature characteristics, but the capacity value was very small. From above results, it can be considered that the thin film of 30% of Nb2O5 and 70% of TiO2 is the best potential with highest capacity value and small changes against the changes of temperature.